1982
DOI: 10.1111/j.1474-8673.1982.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Dopamine Receptors: Physiological, Pharmacological and Therapeutic Implications

Abstract: Dopamine receptor activation can lead to pronounced changes in cardiovascular function. The myriad of effects produced by dopamine receptor agonists results from the activation of dopamine receptors located at different anatomical sites in the cardiovascular system. Further basic research is required to better characterize these dopamine receptors so as to allow the development of more specific dopamine receptor agonists. Endogenous dopamine may be involved in the physiological control of fluid and electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(65 citation statements)
references
References 149 publications
3
62
0
Order By: Relevance
“…The fact that pargyline plus 6-OHDA reduced dopamine/NA ratios in both segments of the mesenteric artery and renal artery, although not significantly for the latter, suggests that dopamine is probably stored in two different neuronal structures which are selectively affected by 6-OHDA. An independent dopaminergic innervation in the main trunk and proximal branches of the mesenteric artery and renal artery is supported also by the studies ofYeh et al (1969), Goldberg (1972);Goldberg et al (1978), Lokhandwala & Buckley, (1977), Lokhandwala & Barrett, (1982), Kullman et al (1983) and Amenta et al (1984) which describe the presence of specific receptors for dopamine in these vascular areas, and by the presence of considerable concentrations of the dopamine metabolites 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) in mesenteric and renal arteries (LackQvic et al, 1982). In addition it has been reported that other vascular and non-vascular peripheral tissues are supplied with nerves where the transmitter substance is dopamine (Bell et al, 1978 a,b;Bell & Rome, 1984;Commissiong et al, 1978;Dinerstein et al, 1979;Lackovic & Neff, 1980).…”
Section: Discussionsupporting
confidence: 67%
“…The fact that pargyline plus 6-OHDA reduced dopamine/NA ratios in both segments of the mesenteric artery and renal artery, although not significantly for the latter, suggests that dopamine is probably stored in two different neuronal structures which are selectively affected by 6-OHDA. An independent dopaminergic innervation in the main trunk and proximal branches of the mesenteric artery and renal artery is supported also by the studies ofYeh et al (1969), Goldberg (1972);Goldberg et al (1978), Lokhandwala & Buckley, (1977), Lokhandwala & Barrett, (1982), Kullman et al (1983) and Amenta et al (1984) which describe the presence of specific receptors for dopamine in these vascular areas, and by the presence of considerable concentrations of the dopamine metabolites 3,4-dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA) in mesenteric and renal arteries (LackQvic et al, 1982). In addition it has been reported that other vascular and non-vascular peripheral tissues are supplied with nerves where the transmitter substance is dopamine (Bell et al, 1978 a,b;Bell & Rome, 1984;Commissiong et al, 1978;Dinerstein et al, 1979;Lackovic & Neff, 1980).…”
Section: Discussionsupporting
confidence: 67%
“…As with a-adrenoceptors on nerve endings, activation of prejunctional dopamine receptors leads to a decrease in the overflow of NA and dopamine from sympathetic nerves, but the blockade of dopamine receptors does not usually produce an increase in the release of the amines (Langer, 1981;Lokhandwala & Barrett, 1982;Willems et al, 1985). This has been observed in the majority of sympatheticallyinnervated tissues and one of the reasons is that the concentration of dopamine attained in the biophase is too low to stimulate the prejunctional dopamine receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been shown that the activation of prejunctional dopamine receptors can also lead to a decrease in transmitter release, most observations do not support the view that, under most conditions, released dopamine activates these receptors (Langer, 1981;Willems et al, 1985). However, it has been suggested (Lokhandwala & Barrett, 1982) that under conditions of continuous nerve stimulation, where the amount of dopamine f-hydroxylase becomes rate limiting, greater amounts of newly synthesized dopamine would be released into the biophase. This would make possible the activation of prejunctional dopamine receptors by the released dopamine, acting as a prejunctional co-transmitter, further intensifying the negative feedback control of transmitter release activated by NA.…”
Section: Introductionmentioning
confidence: 99%
“…The natriuretic effects of DA are generally thought to be due to an increase in renal blood flow and glomerular filtration rate (1) but may include direct tubular effects since low doses of DA increase urine output and urinary sodium excretion without altering renal hemodynamics (3)(4)(5). Although the mechanism of action ofDA within the kidney is not resolved, the effects ofDA on the kidney are blocked by DA receptor antagonists (2,6,7). DA receptors have been classified in the central nervous system as D1 and D2 (8) and in the periphery as DA1 and DA2 (9).…”
mentioning
confidence: 99%
“…Exogenous dopamine (DA) produces a natriuretic/diuretic response in a variety of species, including humans (1,2). The natriuretic effects of DA are generally thought to be due to an increase in renal blood flow and glomerular filtration rate (1) but may include direct tubular effects since low doses of DA increase urine output and urinary sodium excretion without altering renal hemodynamics (3)(4)(5).…”
mentioning
confidence: 99%